Time-resolved fluorescence measurements using self-pulsing 650-nm laser diodes - Matthews, DR; Summers, H; Njoh, K; Errington, R; Smith, P; Ameer-Beg, S; Vojnovic, B (2005)
We report on the development of a stroboscopic excitation technique using a self-pulsing laser, and show that it is a feasible method for obtaining fluorescence lifetime information from a biochip format. The self-pulsing lasers described here are versatile devices which have been used for one photon excitation measurements to determine the lifetime of cyanine 5 in water and ethanol. The same devices have been used to develop a technique whereby the emphasis for time-resolution of a lifetime measurement can be transferred to the excitation source from the detector and processing electronics by virtue of the multiple-pulse, variable frequency nature of the laser output.